Neoliberalizing news discourse: A semio-discursive reading of news gamification. Issue 5 (October 2019) - Magdi Fawzy, Rania
Gamified news is a clear example of contemporary convergent practices which conflate the functionalities of formerly separate entities, video games and journalism. This practice marks a shift in the journalistic norms, positioning journalism and news users within the neoliberal paradigm. In this view, the study proposes a discursive approach to examine how gamified news discourse is colonized by the neoliberal values of marketization and commodification. The analysis takes a case study of Pirate Fishing: An Interactive Investigation, a gamified news launched by Al Jazeera. It is not just the narrative of Pirate that carries ideological bearings, rather the ludic design itself is found to be fit within the neoliberal mentality. Therefore, the ludic semiosis of Pirate Fishing is examined as well. As such, a dialectical relation between discourse, semiotics and neoliberal ideologies, in the context of gamification, is drawn in this article. Based on the analysis, seven interrelated neoliberal discourses are highlighted: 'calculative rationality', 'self-entrepreneurship', 'minimalism', 'aesthetic preferences', 'individualism', 'sovereign consumer' and 'personal responsibility'.